Pelatihan Pengembangan Pendidikan Karakter di Jenjang PAUD untuk Menuju Generasi Emas - Dwiyani Anggraeni; Azimatur Rahmi; Abdi Chairul (Universitas Pahlawan Tuanku Tambusai, 2026)
Education of character building is the most important things for early childhood education. Education of character not only about knowledge but must include morality value to develop a good human character. Education character goals for early childhood education are to make stakeholder child to ready for enter the work activity when their grow up. This training would do at Bimba Rainbow Kids at Cikarang Selatan. The goals of this training to prepare and practice all teachers at early childhood to manage and create education character programs with daily habits and life character practice in classroom activity. This training is give to all teachers at Bimba Rainbow Kids. The Training result early childhood education teachers have knowledge and ability to create and manage characters programs for students, students have a good progress to develop good characters and knowledge of morality value and can control and manage emosional self.